2012
DOI: 10.1371/journal.pone.0043452
|View full text |Cite|
|
Sign up to set email alerts
|

Colorectal Cancer Migration and Invasion Initiated by microRNA-106a

Abstract: MicroRNAs have been implicated in the regulation of several cellular signaling pathways of colorectal cancer (CRC) cells. Although emerging evidence proves that microRNA (miR)-106a is expressed highly in primary tumor and stool samples of CRC patients; whether or not miR-106a mediates cancer metastasis is unknown. We show here that miR-106a is highly expressed in metastatic CRC cells, and regulates cancer cell migration and invasion positively in vitro and in vivo. These phenotypes do not involve confounding i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
56
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 76 publications
(58 citation statements)
references
References 37 publications
(37 reference statements)
2
56
0
Order By: Relevance
“…On the contrary, these cells spread in the perilesional-and CRCderived ECM over time. These findings are in agreement with previous reports indicating an invasive phenotype of these cells in Matrigel 44 and xenograft models. 34,46 Our findings highlight a relevant role of the healthy ECM in constraining the spread of tumor cells with invasive capacity, as LoVo and SW480 cells.…”
Section: Conclusion and Discussionsupporting
confidence: 94%
See 2 more Smart Citations
“…On the contrary, these cells spread in the perilesional-and CRCderived ECM over time. These findings are in agreement with previous reports indicating an invasive phenotype of these cells in Matrigel 44 and xenograft models. 34,46 Our findings highlight a relevant role of the healthy ECM in constraining the spread of tumor cells with invasive capacity, as LoVo and SW480 cells.…”
Section: Conclusion and Discussionsupporting
confidence: 94%
“…43 HT29 cells have been reported to have modest invasive capacity in Matrigel. 44 In vivo, depending on the xenograft model HT29 cells have been reported to remain confined in the tumor mass 44 or invade the surrounding tissue. 44,45 All these findings indicate that the ability of HT29 cells to spread out from the primary site depend on the microenvironment in which they were seeded.…”
Section: Conclusion and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…2), which was in consistent with previous studies that reported high expression of miR-106a in cancer tissues of CRC patients (17,18); meanwhile, compared to NCM640 cells, miR-106a was significantly elevated in SW620 and HT29 cell lines (Fig. 3), which was in line with a previous study (19). These results together suggested the oncogenetic role of miR-106a in CRC patients and in SW620/HT29 cells.…”
Section: Discussionsupporting
confidence: 92%
“…[14][15][16] For example, deregulated miRNA expression has been implicated in aberrant proliferation, genome stability and epithelial-mesenchymal transition. [17][18][19] Analyses of miRNA expression in breast cancer tumor specimens have demonstrated association with specific breast cancer subtypes. Additionally, specific miRNA species are correlated with specific facets of breast cancer biology and prognosis.…”
Section: Introductionmentioning
confidence: 99%